Effect of heat stress on acid-base balance in Polish Merino sheep - K. Wojtas; P. Cwynar; R. Kolacz; R. Kupczynski (Archives Animal Breeding, 2013)
Effect of heat stress on changes in acid-base balance, physiological parameters and cortisol level were evaluated in Polish Merino sheep. Fifteen sheep were exposed to high temperature conditions (30 °C) in order to induce heat stress. All environmental parameters such as temperature, humidity and air movement were monitored. A decrease of partial pressure of CO2 (pCO2) in blood and concentration of total CO2 (tCO2) and an increase of pO2 were observed. The cortisol level also significantly increased. In the next stage of the experiment the soothing effect of air movement was examined. An increased air movement led to reduction of thermal stress. An increase in pCO2 and decrease in cortisol level were observed. The study showed that heat stress leads to changes in acid base balance and cortisol secretion. Air movement has a soothing effect on heat stress in Polish Merino sheep.